Competition scheduling patterns of emerging elite players in professional men's tennis. Issue 18 (17th September 2021) - Perri, Thomas; Duffield, Rob; Murphy, Alistair; Mabon, Tom; Reid, Machar
ABSTRACT: This study analysed the competition scheduling of future top 100 and 250 ranked tennis players from international tournament profiles at ages 13–18y. Retrospective tournament data were analysed for 165 future top 100 (T100) and top 250 (T250) males during their junior international tournament eligibility. Tournament/match volumes, days between tournaments and consecutive tournaments (<8 days between) were quantified for junior and professional events. A two-way (age x ranking) analysis of variance determined the effects of age and ranking group on tournament profiles. Significant interactions were observed for tournament volumes across junior and professional categories, with T100 players competing in professional tournaments earlier ( p <0.05). No significant interactions were observed for volumes of junior or professional matches played ( p >0.05). No significant interactions were observed for days between tournaments or consecutive tournaments played ( p >0.05). Significant main effects were observed for age on tournament volume, with junior and professional volume increasing at age 15 and 17, respectively ( p <0.05). Higher match volumes were observed for T100 players compared to T100-S players ( p <0.05). Competition schedules intensify at age 15 compared with ages 13–14y through increased tournament and match volumes. Future T100 players' transition to professional tournaments earlier, alongside greater engagement in higher quality junior tournaments.